Analisis Kendala Pengajaran Volume Tabung di SD dan Strategi Inovatif Berbasis teknologi bagi Calon Guru - Syakila Jihan Fadilah; Angelika Tia Miranti; Neza Agusdianita (PT. Hasba Edukasi Mandiri, 2025)
Mathematics learning, especially in topics like geometry and measurement such as the volume of a cylinder, often presents challenges for elementary school students. This study aims to analyze the obstacles in teaching the volume of a cylinder in elementary schools, identify the root causes of students' difficulties, and present strategic implications for future teachers. The research method used is qualitative with data collection techniques in the form of structured interviews. Data were collected through interviews with 4th-grade teachers at SDN 44 Kota Bengkulu. The results of the interviews showed that the teachers had used demonstration methods supported by visual media (videos, pictures, real-life illustrations, and interactive activities). Students were encouraged to observe real objects in the shape of cylinders (such as water bottles, milk cans, and drinking glasses) and derive the formula for the volume of a cylinder from its net. Although a variety of media were used, the main challenges faced included limited teaching time and inappropriate teaching methods. These obstacles impacted students' learning outcomes, causing conceptual difficulties, calculation errors, and an inability to solve word problems with contextual applications. Students often struggled to visualize the real-world applications of the volume of a cylinder. Teachers hope that future mathematics teachers will not only understand the theory conceptually but also be able to apply it critically and creatively, as well as utilize technology as an effective and innovative learning medium. Strategies for future teachers include leveraging technology to connect abstract concepts to real-world problems to address the existing challenges.